2014
DOI: 10.3310/hsdr02170
|View full text |Cite
|
Sign up to set email alerts
|

Transitions at the end of life for older adults – patient, carer and professional perspectives: a mixed-methods study

Abstract: BackgroundThe end of life may be a time of high service utilisation for older adults. Transitions between care settings occur frequently, but may produce little improvement in symptom control or quality of life for patients. Ensuring that patients experience co-ordinated care, and moves occur because of individual needs rather than system imperatives, is crucial to patients’ well-being and to containing health-care costs.ObjectiveThe aim of this study was to understand the experiences, influences and consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 74 publications
1
57
0
Order By: Relevance
“…Hospitalisation for acute management will still be appropriate for older people, for example, those with a displaced fractured neck of femur. Family carers and those in care coordinating roles (such as the GP) are key supports in determining whether acute care transitions occur 10. Decreasing hospitalisation rates therefore must focus on preventable, not all, admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalisation for acute management will still be appropriate for older people, for example, those with a displaced fractured neck of femur. Family carers and those in care coordinating roles (such as the GP) are key supports in determining whether acute care transitions occur 10. Decreasing hospitalisation rates therefore must focus on preventable, not all, admissions.…”
Section: Discussionmentioning
confidence: 99%
“…For residents with palliative care needs who are not dying, avoiding hospitalisation remains an important outcome. Hospitalisation does not necessarily improve symptom management or quality of life, and adds burden to family members 9 10. Avoidable hospitalisations are contributed to by inadequate residential facility staff training and education,11–13 complex prognostication14 15 and lack of understanding by residents and families of the consequences of hospitalisation in the palliative phase 11 16 17…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] However, enrolling a patient into hospice can significantly alter the dynamics of the treating physician and patient, given that a majority of the care is provided at home and delivered by a dedicated hospice team. One can imagine that patients and caregivers who have established trusting relationships with their physicians and affiliated hospitals would want to continue to receive care from them under certain circumstances, even after enrollment into hospice.…”
Section: Hospitalization Of Home Hospice Patients 263mentioning
confidence: 99%
“…It is a challenging and demanding role which few people aspire to, but which may be thrust on them. Despite policy initiatives13 14 to address these caring demands, a large study on transitions between places of care near end of life reported that in 2013 little has changed to improve family carers’ experiences 15…”
Section: Introductionmentioning
confidence: 99%